1986
DOI: 10.1063/1.865727
|View full text |Cite
|
Sign up to set email alerts
|

New analytical solution for an ion-acoustic soliton in a two-ion plasma

Abstract: A new analytical solution is obtained for an ion-acoustic soliton, which is much closer to the exact solution than the Korteweg–de Vries (KdV) solution. The case of a two-ion plasma is considered in detail, and the results are compared with those of the dressed soliton solution. The effect of multiple ionization of the ion species is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In this paper ion heating in connection with parametric decay at the beat frequency has been discussed and explained analytically as heating by parametrically excited low-frequency ion-Bernstein waves (Tripathi & Sharma 1988) in a multi-ion-species plasma (Dash, Sharma & Buti 1984;Sharma, Yashvir & Bhatnagar 1986;Milic & Krstic 1987). It has been found that the growth rate can be controlled by several parameters, such as the mass, density and temperature of two ion species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this paper ion heating in connection with parametric decay at the beat frequency has been discussed and explained analytically as heating by parametrically excited low-frequency ion-Bernstein waves (Tripathi & Sharma 1988) in a multi-ion-species plasma (Dash, Sharma & Buti 1984;Sharma, Yashvir & Bhatnagar 1986;Milic & Krstic 1987). It has been found that the growth rate can be controlled by several parameters, such as the mass, density and temperature of two ion species.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the low system efficiency, ionospheric experiments detect signals at comparable levels. The beating of two high-frequency electromagnetic waves gives rise to the radiation of a whistler at a frequency 6-28 x 10 5 rad s * (Shoucri et al 1982). Taking parameters typical of the auroral ionosphere,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations